Poultry waste in isonitrogenous and isoenergetic diets for finishing swine - Bellaver, Claudio; Fialho, Elias Tadeu; Protas, José Fernando (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out to evaluate the biological and economic effects of adding poultry waste for finishing pigs. The 200 crossed Landrace x Large White barrows, started the test with 51.39 ± 0.20 kg and ended with 92.75 ± 1.04 kg. The experimental design was the completely randomized with four treatments and five replications. The treatments were, inclusions of 0, 5, 10 and 15% of poultry waste in isonitrogenous and isoenergetics diets for finishing swine. The above percentages in sequence showed mean daily weight gans of 831 ± 25, 753 ± 33, 764 ± 22 and 759 ± 29 g and feed gain ratios of 3.30 ± 0.074, 3.56 ± 0.042, 3.44 ± 0.062 and 3.49 ± 0.106 without significative differences (P>0.05). Negative significant linear effects (P<0.05) for digestible dry matter, (DDM = 89.353 - 0.540 X: R2 = 0.86), crude protein digestibility coefficient (CPDC = 86.053 - 0.593 X; R2 = 0.68), digestible energy (DE = 3916.230 - 8.553 X; R2 = 0.39), dressing percentage (DP = 75.620 - 0.163 X; R2 = 0.20), cool carcass weight (CCW = 73.908 - 0.468X; R2 = 0.20) and. loin lard thickness (LLT = 3.438 - 0.048 X; R2 = 0.22). The lower cost was for the treatment without poultry waste, but prices of ingredients could change and promote the use of this byproduct.